2019
DOI: 10.3892/etm.2019.7190
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of microRNA‑374a predicts poor prognosis in human glioma

Abstract: Certain microRNAs (miRNAs/miRs) may be used as prognostic biomarkers in various types of cancer. The purpose of the present study was to identify miRNAs that were abnormally expressed in glioma of different grades, and to evaluate their clinical implications in patients with glioma. The differentially expressed miRNAs were evaluated from the expression profiles of six glioma tissues (three low-grade and three high-grade gliomas) determined using a microarray platform. Reverse transcription-quantitative polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
2
2
0
Order By: Relevance
“…This study found up-regulation of miR-374 along with its target gene AKT in low grade glioma. The findings of the current study were also corroborated by Dong et al demonstrated who showed that miR-374 level was significantly repressed in high-grade vs. low-grade gliomas which is consistent with the results of the present study [30]. Similarly, Zhang, et al [31] , reported that miR-374 activates the PI3K/Akt pathway in myocardial damage thus autophagy reveals a novel function for miRNA in a critical cellular event with significant impacts on cancer development, progression, and treatment, and in other diseases [32].…”
Section: Discussionsupporting
confidence: 93%
“…This study found up-regulation of miR-374 along with its target gene AKT in low grade glioma. The findings of the current study were also corroborated by Dong et al demonstrated who showed that miR-374 level was significantly repressed in high-grade vs. low-grade gliomas which is consistent with the results of the present study [30]. Similarly, Zhang, et al [31] , reported that miR-374 activates the PI3K/Akt pathway in myocardial damage thus autophagy reveals a novel function for miRNA in a critical cellular event with significant impacts on cancer development, progression, and treatment, and in other diseases [32].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, it has been implicated in resistance to treatment, both against chemotherapy and radiotherapy This study found up-regulation of miR-374 along with its target gene AKT in low grade glioma. The ndings of the current study were also corroborated by Dong et al demonstrated who showed that miR-374 level was signi cantly repressed in high-grade vs. low-grade gliomas which is consistent with the results of the present study [29]. Similarly, Zhang, et al [30] , reported that miR-374 activates the PI3K/Akt pathway in myocardial damage thus autophagy reveals a novel function for miRNA in a critical cellular event with signi cant impacts on cancer development, progression, and treatment, and in other diseases [31].…”
Section: Discussionsupporting
confidence: 93%
“… 44 The expression of hsa-miR-374b-5p, which was newly identified in this study, was found to be a poor prognostic factor in human glioma. 45 These results suggested the reliability of our study.…”
Section: Discussionsupporting
confidence: 70%